Usage of biotesting method for evaluation of the quality of water in the Central Caspian part - S. A. Guseynova (Юг России: экология, развитие, 2015)
In the article the estimation of monitoring of Caspian Sea and a role of a method of the biotesting of the quality definition of the water is certain.